2016
DOI: 10.1155/2016/2617473
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Content of “Bowl Water” Used for Communal Handwashing in Preschools within Accra Metropolis, Ghana

Abstract: Objective. This study aimed at determining the microbial content of “bowl water” used for communal handwashing in preschools within the Accra Metropolis. Method. Six (6) preschools in the Accra Metropolis were involved in the study. Water samples and swabs from the hands of the preschool children were collected. The samples were analysed and tested for bacteria, fungi, parasites, and rotavirus. Results. Eight different bacteria, two different parasites, and a fungus were isolated while no rotavirus was detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Recent studies in Accra have isolated K. oxytoca from Cyperus esculentus L. (tiger nuts) which were claimed to have been washed and which were being sold at local markets [57]. K. oxytoca has also been isolated from water used for hand-washing in preschools in the Accra, leading researchers to believe that the bacterium may be present in local water sources [29]. Moreover, studies in West Africa and Ghana have found faecal contamination of produce to be quite common [58], suggesting that the contamination observed in the present study should not be regarded as surprising.…”
Section: Contamination Of M Oleiferamentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies in Accra have isolated K. oxytoca from Cyperus esculentus L. (tiger nuts) which were claimed to have been washed and which were being sold at local markets [57]. K. oxytoca has also been isolated from water used for hand-washing in preschools in the Accra, leading researchers to believe that the bacterium may be present in local water sources [29]. Moreover, studies in West Africa and Ghana have found faecal contamination of produce to be quite common [58], suggesting that the contamination observed in the present study should not be regarded as surprising.…”
Section: Contamination Of M Oleiferamentioning
confidence: 99%
“…However, for a soap to simply remove bacteria from hands is not enough. In humanitarian and resource-limited settings where water is routinely scarce, water used for hand-washing is often reused [29][30][31][32][33][34][35]. Accordingly, understanding what happens to bacteria that have been removed from hands is of extreme importance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations